(untitled) (Vietnam Journal of Community Medicine, 2021)
The study was carried out on 7117 second-year students of Hanoi Medical University in the period 2010-2019. Objective: Describe the nutritional status of 2nd year students in the period 2010-2019. Methods: Cross-sectional description of multiple time points. Results: During the 10-year period (2010-2019) in the studied group of students, there was an acceleration in height increase of 2.29 cm for men and 0.25 cm for women; weight gain acceleration 4.56 kg for men and 1.50 kg for women. In general, the average height and weight of students living in the city is higher than the ones in the countryside; the rate of CED decreased (down 4.5%), the acceleration is more in the city than in the rural area; the rate of TCBP increased (up 3.9%) and the rate of increase is higher in cities than in rural areas.